A curriculum tailored for workers? Knowledge organization and possible transitions in Swedish VET. Issue 5 (2nd September 2016) - Nylund, Mattias; Rosvall, Per-Åke
Abstract: A key feature of the Swedish upper secondary school reform of 2011 (GY11) is the new direction it sets out for the organization of vocational education (VET) and the role it plays in youths' transitions from school to work. This study analyses the GY11 reform in terms of its impact on the organization of knowledge in VET and its implications for students' prospects of transitioning from VET to work or higher education, and for their roles as citizens. To understand its likely consequences, GY11 is analysed in the context of practices in a school class for the Vehicle programme steered by the curriculum prior to GY11. The theoretical concepts used are drawn from Basil Bernstein and his distinctions between knowledge organized into horizontal and vertical discourses. The findings of the study suggest that GY11 reinforces an already strong emphasis on horizontally organized knowledge in VET by placing great importance on strongly context-bound, skill-oriented knowledge. This implies a stronger exclusion of VET students, primarily with working-class backgrounds, from vertical discourses and limits the possible transitions of youths taking the VET-route by reducing their access to higher education and their capacity to function as both workers and citizens.